Sediments contamination with organic micropollutants: current state and perspectives = Zanieczyszczenie osadów dennych mikrozanieczyszczeniami organicznymi: stan aktualny i perspektywy - Popenda, Agnieszka; Włodarczyk-Makuła, Maria (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This study focused on the sediment contamination with some organic micropollutants based on the monitoring data together with available literature in Poland. The following persistent organic pollutants (POPs): polycyclic aromatic hydrocarbons (PAHs), polychlorinated biphenyls (PCBs) and chlorinated pesticides (CP) were characterized in sediments with respect to current legislations in force.
Keywords: osady denne; WWA; PCB; pestycydy chloroorganiczne; zanieczyszczenia; sediments; PAHs; PCBs; chlorinated pesticides